The Effect of Rice Bran Utilization in Planting Media on Increasing Oyster Mushroom Production (Pleurotus Ostreatus) in Konawe District - Saleh, Leni; S Salahuddin; Malik, Nurhayu (Demeter: Journal of Farming and Agriculture, 2024)
This study aims to determine the effect of using rice bran on the production of white oyster mushrooms with sawdust media used by farmers in oyster mushroom farming in Tongauna District, Konawe Regency. The design used is a Completely Randomized Design (CRD). Data collection by observing and recording the results of observations. To see the effect of using rice bran on the white oyster mushroom planting medium, analysis of variance (ANOVA) was carried out. With linear regression. This stage is the stage for processing the results of data collection in the experiments that have been carried out. The data that has been obtained is presented in table form. with the Oneway ANOVA Test with a confidence level of 5% and to see the effect of using rice bran on the white oyster mushroom planting medium, analysis of variance (ANOVA) was carried out. If the analysis of variance of the treatment is significantly different, then a Further Test is carried out with a Turkey distance at a level of 5%. Based on the results of the study, it showed that the results of the OneWay Anova Test and the Turkey Test had an effect on mycelial growth with the addition of rice bran to the composition of the oyster mushroom planting medium, the concentration of rice bran in the composition of the planting medium that is best used for mycelial growth is a concentration of 40%.